Pengembangan Sistem Manajemen Inventaris Laboratorium Rumah Sakit Berbasis Web (Studi Kasus: Laboratorium Rumah Sakit Jiwa Prof.Dr.Soerojo Magelang) - Tesa Putri Cendani; Denny Sagita Rusdianto; Heru Nurwarsito (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Laboratory of Prof.Dr.Soerojo Magelang Mental Hospital is medical support installation that has a function of serving the community to carry out examinations in diagnosing, healing, and recovering diseases. Operational and productivity in the laboratory need to be supported by good inventory management. However, this laboratory has several problems in inventory management. The main problem is finding a stock card to use an item which take a lot of time, so that the officers often make use of the item even before writing it in the stock card, it causses disrepancy between the physical data and data in the list. In the other hand, the receipt data records is written conventionally inside a book which causes the records to be piled up. Because of there are too many number of item, makes the recapitulation of the received and used items will be prone to errors. To reduce these problems, a system that could manage laboratory inventory should be developed. This system was developed based on web and using codeigniter framework with progressive web application technology to provide easy access. This research resulted in 91 functional needs and 1 non-functional needs with the features of managing demand, receipt, use, and report. The results of the system testing on unit testing produced valid status in 3 sample units, integration testing produced valid status, validation testing produced valid status on 91 needs and the alternatives, and compatibility testing shows that the system is free from critical issues so means that the system meet the compatibility aspect.